The fundamentals of electrical engineering : for mechatronics - Hüning, Felix, 1971- (De Gruyter, 2014)
This book covers the basic principles of electrical engineering. The depth of content and presentation is intended for students in the field of mechatronics, especially those with a background in mechanics or mechanical engineering. In addition to theoretical sections and practical applications, the textbook offers numerous practice exercises to apply and deepen the student's learning.